Protecting the children: An indigenous response from churches in South Africa - Botha, MJ (Nederduitse Gereformeerde Teologiese Tydskrif, 2010)
According to UNICEF, the HIV/AIDS pandemic contributes to the estimated 143 million orphans in 93 developing countries. The Vana Vetu programme is an indigenous grassroots response to the challenge of addressing these orphans’ needs by women in four Anglican Church dioceses in the Eastern Cape Province. In this article the Vana Vetu programme is evaluated according to the five core principles outlined in “The framework for the protection, care and support of orphans and vulnerable children living in a world with HIV and AIDS” (UNICEF) and concludes that Vana Vetu aligns with all five action areas and consequently aligns with both the national and international discourses on OVC. As such this programme is an example of a planned intervention as a religious response, which increases the relevance of churches, and church organisations as key role players in welfare and development in the South African context.